2023
DOI: 10.3389/fpls.2023.1229157
|View full text |Cite
|
Sign up to set email alerts
|

Organic waste compost and spent mushroom compost as potential growing media components for the sustainable production of microgreens

Abstract: Microgreens are emerging specialty crops becoming increasingly popular for their rich nutrient profile and variety of colors, flavors, and textures. The growing medium is a significant key factor in microgreen yield, quality, and sustainability. The widespread use of peat-based media raises questions regarding the environmental sustainability of microgreens production, and new substrates that are more sustainable are required. To this purpose, a study was designed with the objective of comparing eight alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
6
2
2
Order By: Relevance
“…Examining the content of Mn and Cu, their content was consistent with the range of concentrations observed by Xiao et al (2016) and Di Gioia et al (2019a) in Brassicaceae species, while Kyriacou et al (2021a) reported much higher Mn content for four Brassica rapa L. microgreens. For sunflower, Poudel et al (2023b) reported values of Mn and Cu slightly lower than those observed in the present study on a DW basis. On the other hand, Corrado et al (2021) reported higher levels of Mn and much lower levels of Cu in borage microgreens compared to the levels observed in this study.…”
Section: Variation Of Micromineral Concentrationcontrasting
confidence: 97%
See 1 more Smart Citation
“…Examining the content of Mn and Cu, their content was consistent with the range of concentrations observed by Xiao et al (2016) and Di Gioia et al (2019a) in Brassicaceae species, while Kyriacou et al (2021a) reported much higher Mn content for four Brassica rapa L. microgreens. For sunflower, Poudel et al (2023b) reported values of Mn and Cu slightly lower than those observed in the present study on a DW basis. On the other hand, Corrado et al (2021) reported higher levels of Mn and much lower levels of Cu in borage microgreens compared to the levels observed in this study.…”
Section: Variation Of Micromineral Concentrationcontrasting
confidence: 97%
“…Boron content was on average 0.34 mg 100 g -1 FW and ranged between a minimum of 0.08 mg 100 g -1 FW in borage and a maximum of 0.18 mg 100 g -1 FW in lemon balm microgreens, except for scallion microgreens that had a much higher B content (0.37 mg 100 g -1 FW) compared to all the other species. Very limited information is available in the literature on the variation of B content in microgreens, but in the case of sunflower, similar levels were observed by Poudel et al (2023b) in sunflower shoots derived from untreated seeds. Conversely, D'Imperio et al ( 2021) observed B levels nearly three times higher in mizuna microgreens grown in peat and fertilized with half-strength Hoagland nutrient solution.…”
Section: Variation Of Micromineral Concentrationmentioning
confidence: 70%
“…In line with the dietary recommendation and society’s increasing interest in healthy eating, there has been an increase in demand for fresh, functional, and nutraceutical foods while still being delicious ( Kyriacou et al., 2016 ). Microgreens, with their diverse range of colors, flavors, and textures along with their rich nutrient profile, are gaining popularity as emerging specialty crops ( Poudel et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The time from seeding to harvest is crop dependent and may vary from one to three weeks ( Di Gioia et al., 2017 ). Based on their age or size during harvesting and consumption, sprouted seeds can be categorized as sprouts (youngest and shortest), microgreens (intermediate, about 2 inches tall and harvested within 7-14 d), and baby greens (oldest and largest, 3-4 inch tall) ( Kou et al., 2014 ; Poudel et al., 2023 ). A widely accepted definition of microgreens is “Tender immature greens produced from seeds of vegetables and herbs having fully developed cotyledons with or without the emergence of a rudimentary pair of first true leaves” ( Xiao et al., 2012 ; Senevirathne et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation